KONFLIK KPK VS POLRI JILID III: KONTESTASI KUASA DALAM PENEGAKAN HUKUM DI INDONESIA - Asep Abdul Sahid (Faculty of Sharia and Law, Sunan Gunung Djati Islamic State University of Bandung, 2016)
Komisi Pemberantasan Korupsi (KPK) and Polisi Republik Indonesia (Polri) are two state law enforcement institutions. Indeed both institutions can carry out the organization of law enforcement, particularly in combating corruption, in shoulder to shoulder. But less than a decade, both institutions practice it often indicates that fights enemy volumes. The aims of the sstudy in this paper is to identify, to analyze, and to formulate how the KPK-Polri has a relations in a configured-usurpation than shoulder to shoulder in law enforcement. The corpus study is a series of events conflicts KPK vs Polri Volume III, triggered by the determination of Commissioner General Budi Gunawan as a suspect and arrest event Widjojanto by the Police as well as efforts to make the entire leadership of the KPK suspects. This study indicates the charge contestation or dispute the power ini law enforcement eradication of corruption. The indicators include conjoined twins jurisdictions, law enforcement power struggle, and political events set in law.